THE IMPLEMENTATION OF COLLABORATIVE WRITING IN IMPROVING STUDENTS WRITING SKILL AT 11TH GRADE OF SCIENCE CLASS AT SMA PERTIWI AMBON - Bella C. F Camerling (JURNAL TAHURI, 2020)
As one of productive skill in the foreign language context, writing skill can be figured as the most difficult skill for EFL learners. Therefore EFL teachers should implement meaningful teaching technique to help learners improve their writing skill. One of the techniques that recommended by the experts is collaborative writing. It is the teaching technique which is focused on work collaborative in writing process. This technique is adapted from the collaborative learning strategy in which this technique is useful to treat students to work collaboratively in writing process. The collaborative works can be done in pairs or in a group. Therefore, this study is aimed at describing the useful of implementing collaborative writing technique in improving the students’ writing skill. The research consists of the subject from SMA Pertiwi Ambon comprised of 13 students in XI-Science class. The data was collected from classroom observation and field notes, test, questionnaire and interview. The research methodology that used in this research was classroom action research under mix method qualitative-quantitative design. The findings of the study revealed that by implementing the collaborative writing technique, the students can improve their writing skill and it can be shown through the result of their writing paragraphs. Through the implementation of this technique, the students can share their ideas, organize their ideas, write the outline and develop their writing after they work both in pairs or in a group. They also did a peer feedback, revise and write their final product of their writing. Moreover, they have positive respond towards this technique and build a good interaction in working on their writing paragraphs. As the conclusion, this technique is useful to be implemented in classroom writing activities. To implement this technique optimally, teachers need to consider the characteristics of students background knowledge on writing in English, the given topic and the time for learners to practice their writing skill. The more the students have chance to work collaborative the better they produce their writing skill.